Clarisa Product Quality Control Using Methods Lean Six Sigma and Fmeca Method (Failure Mode And Effect Cricitality Analysis) (Case Study: Pt. Maspion Iii) - Achmad Rifki Andriansyah; Wiwik Sulistyowati (Universitas Muhammadiyah Sidoarjo, 2020)
PT. Maspion III is a company engaged in household appliances products, In carrying out its production process activities PT. Maspion III experiences various problems. Clarisa products are products that are found reject or defective. because it is caused by suboptimal quality control. This can be seen from the number of reject or defect products. This study aims to determine the type of waste that causes defects, determine the capability of the production process, and provide recommendations for improvement in the production process. The research methods are quantitative and qualitative approaches to lean six sigma and yang and FMECA (Failure Mode and Effect Criticality Analysis). lean six sigma is a systemic and systematic approach to identifying and eliminating waste. FMECA (Failure Mode and Effect Criticality Analysis) is used as a reference for companies to take corrective actions to identify product critical points in the production process. The results obtained are waste that affects product quality, namely waste defect, there are two highest defects, namely floi with a cumulative presentation of 51% and a breakage of 65%. In August the capability process is 1.5012, In September the capability process is 1.6818, In October the capability process is 1.3727, In November the capability process is 1.4275, In December the capability process is 1.4366